Dietary advanced glycation end products intake and cardiometabolic risk in overweight adults - Tavares, Juliana Ferreira (2018)
Obesity has reached epidemic proportions worldwide and it is considered a severe public health problem. Overweight is associated with inflammation and oxidative stress, leading to chronic diseases manifestation. The results of recent studies suggest that advanced glycation end products (AGEs), in turn, may favor inflammation and oxidative stress occurrence. Therefore, the consumption of diets rich in AGEs may be involved in the pathogenesis of chronic diseases. Although the effect of the consumption of dietary AGEs has been investigated in animals and humans with diabetes and impaired renal function, studies in overweight healthy subjects are scarce. Therefore, we conducted a systematic review in which we critically analysed clinical studies that evaluated the effects of dietary AGEs on overweight related complications. We also conducted a cross-sectional study to explore the associations between dietary AGEs versus cardiometabolic risk markers in healthy overweight adult subjects. In our systematic review we verified that dietary AGEs restriction seems to improve anthropometric, glycemic, cardiometabolic and inflammatory markers, suggesting that it may be a therapeutic strategy to promote health and prevent chronic diseases. In our cross-sectional study, we estimated the habitual dietary AGEs intake using a Quantitative Food Frequency Questionnaire to assess our subject’s previous six months food intake. We also assessed blood pressure, biochemical variables, homeostatic model assessment for insulin resistance (HOMA-IR), besides the concentrations of inflammatory, and oxidative stress markers. Dietary AGEs consumption was positively associated with malondialdehyde concentrations, an oxidative stress and lipid peroxidation marker, regardless of habitual physical activity, sex, body mass index, energy intake and macronutrients intake. Since oxidative stress is a condition implicated in chronic diseases pathogenesis and overweight subjects are already at high risk of developing such conditions, it is imperative to establish a safe recommendation on dietary AGEs intake and to further explore the molecular mechanisms underlying dietary AGEs and chronic diseases development.